Association Between Eco-Anxiety and Civic Engagement Among University Students in Jakarta: The Moderating Role of Institutional Trust - Suparman, Aman; Amir, Zahra; Munandar, Ervin (HM Publisher, 2026)
Climate change has emerged as one of the most pressing global challenges, generating widespread psychological distress among younger populations. This cross-sectional study examined the association between eco-anxiety and civic engagement among 412 university students recruited from three universities (University A, University B, and University C) in Jakarta, Indonesia, and investigated the moderating role of institutional trust. Data were collected using validated questionnaires measuring eco-anxiety, civic engagement, institutional trust, environmental organization membership, social media exposure, self-efficacy, and demographic variables. Among the 412 respondents (mean age 21.3 ± 2.1 years; 55.3% female), 137 (33.3%) demonstrated high civic engagement. Multivariate logistic regression revealed that institutional trust was the strongest predictor (aOR=5.82; 95% CI: 3.41–9.93; p<0.001), followed by environmental organization membership (aOR=4.27; 95% CI: 2.63–6.93; p<0.001), eco-anxiety (aOR=3.84; 95% CI: 2.31–6.38; p<0.001), self-efficacy (aOR=2.96; 95% CI: 1.82–4.81; p<0.001), and social media exposure (aOR=2.43; 95% CI: 1.47–4.02; p=0.001). The interaction between eco-anxiety and institutional trust was statistically significant (OR=1.42; 95% CI: 1.01–1.99; p=0.043). Stratified analysis showed that among students with high institutional trust and high eco-anxiety, 94.4% demonstrated high civic engagement compared to 33.3% among those with low trust and low eco-anxiety. The model demonstrated excellent discriminative ability (AUC=0.879) and adequate fit (Hosmer-Lemeshow p=0.538; Nagelkerke R²=0.42).